Factores asociados a depresión moderada o severa durante quimioterapia en el Instituto Regional de Enfermedades Neoplásicas Norte - Rojas Gutiérrez, Lyszan Kimberline (2020)
Objective: Identify what factors are associated with moderate or severe depression during chemotherapy in the North IREN. Materials and methods: Observational, analytical, case-control study, conducted on patients treated at the IREN Norte Chemotherapy Service. A questionnaire prepared by the author was applied, structured in sociodemographic characteristics and Beck depression inventory, in addition to data taken from the clinical history. Results: 130 valid surveys were obtained, of these, 58 patients were classified as cases and 72 as controls. In the bivariate analysis, a statistically significant association was found between moderate or severe depression and age, employment status and oncological treatment time. However, in the multivariate analysis only a statistically significant association was found between these levels of depression and age and employment status. Conclusions: Age and employment status are associated with moderate or severe depression during chemotherapy in the Northern IREN.